Precise localization of human beta-globin gene complex on chromosome 11. - Gusella, J (1979)
Cloned DNA probes were used in combination with a panel of five hybrid cell clones containing a series of different terminal deletions in human chromosome 11 to map precisely the human hemoglobin beta and delta chain structural genes contained on this chromosome. The region of deletion in each clone of the panel has been defined by biochemical, immunologic, and cytogenetic markers. DNA from clones containing successively larger terminal deletions was tested with appropriate DNA probes to determine the point on the chromosome at which DNA for these two closely linked hemoglobin genes is deleted. These genes, and by inference the closely linked G gamma and A gamma globin genes as well, have been assigned to the intraband region 11p1205 leads to 11p1208 on the short arm of chromosome 11, an interval containing approximately 4500 kilobases of DNA. The approach appears to have potential for even greater resolution and reasonably wide applicability for gene mapping.